Annie - Meehan, Thomas (Penguin Audio, 2014)
An orphaned girl tries to find her parents, who went missing in 1922
Compact discs
Keywords: Geschichte 1933; Little Orphan Annie (Fictitious character) / Fiction; Orphans / Fiction; Missing persons / Fiction; Little Orphan Annie (Fictitious character); Manners and customs; Missing persons; Orphans; Alltag, Brauchtum; Suche; Waisenkind; Mädchen -- 11 Jahre; Eltern; United States / Social life and customs / 1918-1945 / Fiction; United States; USA; Hörbuch; Jugendbuch; CD